THE EFFECT OF MAGIC-SQUARE GAME IN IMPROVING 10th GRADER STUDENTS’ SPEAKING ACHIEVEMENT - Marisa Sitompul; Tjut Ernidawati (Universitas Negeri Medan, 2015)
This Study was an experimental research. The objective was to discover thesignificance of using magic square game in improving 10th grader students’speaking achievement. Twenty students were taken as the sample: 10 students forthe experimental group and 10 students for the control group. The students in theexperimental group were given magic square game as the media to practice theirspeaking skill. The magic square game was used to improve students’achievement in speaking, while the control group were taught without the magicsquare game. They only use textbooks. The students’ performance were evaluatedby using Fulcher’s (2003) Foreign Service Institute (FSI) Weighting Table. Thescoring was done by the English teacher and the researcher. The research findingsshows that the reliability of the test was high, i.e. 0,99, whereas the T-observedvalue at the level of significance 0,05 is 20 and it was lower than the T-critic(22).Therefore, the alternative hypothesis was accepted. It can be concluded that thestudents’ speaking achievement taught by using magic square game wassignificantly higher than those whom taught without using magic square game. So,English teacher are suggested to use magic square game in practicing the students’speaking achievement.Key words: Magic-Square game, Speaking Achievement